An investigation of data storage security issues on cloud computing in Sumber Puncak Sinergi Sdn Bhd (SPS) / Siti Fatimah Mohd Zuki - Mohd Zuki, Siti Fatimah (2016)
Cloud computing data storage these days has become very popular among the new IT users-individuals and organizations. Organizations particularly find in cloud computing data storage a very flexible and convenient method to access and obtain data. Most companies have chosen to move or migrate their data to the cloud data storage providers as they can minimize the cost of their IT data storage, on the one hand, and save time to backup systems as it is provided by their cloud data storage providers, on the other. Having said that, the issue these days is not about how to store data; the issue is how safe and secure the data is in the hands of their cloud data storage providers. In this research study, the researcher investigates cloud data storage security issues in a Malaysian organization and provides recommendations that would help organizations making better security-related choices. The methodology used in conducting this study is mainly qualitative as the researcher does not merely intend to provide frequencies alone, but, nevertheless, providing hands-on in-depth explanations and interpretations that would provide empirical explanations, suggestions and recommendations. This study found that the current cloud data storage in SPS needs improvements related to security issues. The current cloud data storage provider did not specifically state the location of storing the data, which may cause a breach or an unauthorized access to the private and confidential files and stored data. The outcome of this study would benefit the company under investigation and similar companies that use similar methods to store their data using cloud computing data storage services.